b-6/9=b/3

Simple and best practice solution for b-6/9=b/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for b-6/9=b/3 equation:



b-6/9=b/3
We move all terms to the left:
b-6/9-(b/3)=0
We add all the numbers together, and all the variables
b-(+b/3)-6/9=0
We get rid of parentheses
b-b/3-6/9=0
We calculate fractions
There is no solution for this equation

See similar equations:

| x=-2+8/11 | | X+0.17x=9 | | 8+p=26 | | e-4=-4 | | -2n+6=24 | | 8x-41+6x+1=180 | | 6(c-13)=-36 | | 6(x+2)=6x+23 | | 2=(10x+1) | | 2x-20+1=61 | | 4(p-1)=5p | | 3p-2=-35 | | M2=(10x+1) | | 5+d=-5 | | 2/6=1/9y | | 7(8x+3)=5x+21 | | -9q-9=18 | | y=57y+5 | | 9. 5z–2=2(3z–4) | | 1.4x-2=22-8x | | 7k-2=-6+7k | | -3(w+20)–2w=25 | | F(-2)=6-2x | | 0.5(3x+2)=0.25 | | 5x+17=−7(x+1) | | 2^4*2^-6=2^n | | 6x+29=−97−3x | | X^2x-32=4x | | 2x+(x+8)+2x=90 | | 3x+8+x=2+2x | | 2x(3)=12 | | z/5+2=-85 |

Equations solver categories